2x-6=12+4x

Simple and best practice solution for 2x-6=12+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-6=12+4x equation:


Simplifying
2x + -6 = 12 + 4x

Reorder the terms:
-6 + 2x = 12 + 4x

Solving
-6 + 2x = 12 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-6 + 2x + -4x = 12 + 4x + -4x

Combine like terms: 2x + -4x = -2x
-6 + -2x = 12 + 4x + -4x

Combine like terms: 4x + -4x = 0
-6 + -2x = 12 + 0
-6 + -2x = 12

Add '6' to each side of the equation.
-6 + 6 + -2x = 12 + 6

Combine like terms: -6 + 6 = 0
0 + -2x = 12 + 6
-2x = 12 + 6

Combine like terms: 12 + 6 = 18
-2x = 18

Divide each side by '-2'.
x = -9

Simplifying
x = -9

See similar equations:

| 15+5x=30 | | 6x-3=13+2x | | 9[y]=27 | | 3/5,4/9,11/15 | | [y]2=28 | | -5[y]=-25 | | (3x-4)(2x+3)=0 | | x=137-173 | | 173-137= | | 17-x=1/3(21) | | 3t-8/2=4t | | 4m^2-11m-45=0 | | 3t-9/2 | | 7.2*10^4/9.4*10^-11 | | 5w+9.9=4.9+8w | | 5m^2-34m-48=0 | | 3(x+2)+27=60 | | x+2/x-3 | | (3x^2-5x-6)+(5x^2+4x+4)= | | 7y^2+51=0 | | 1.2(b-10)=50 | | 4+3x=8x+24 | | 4t+14=6t/5 | | 7x-3=4x-9 | | 5x-12/-3=-6 | | 7w-3w=2(3w+11) | | -6=m-2 | | 82=-2+6(v+6) | | -6=m | | 4y+7y=-99 | | -3=n | | 4a+6=90 |

Equations solver categories